Trans-Arterial Embolization of a Giant Hepatic Hemangioma Prior To Surgical Resection – A Case Report and Review of the Literature - Pozotou, Ioanna; Moulazimi, Anastasia; Charalambous, Stavros; Poullos, Nektarios; Loizou, Marios; Christophides, Thalis (Archives of Clinical and Medical Case Reports, 2024)
Hepatic hemangiomas are the most common benign tumors of the liver. The majority of them consist of small and asymptomatic hemangiomas that could be managed conservatively. However, giant hemangiomas with persistent symptoms, rapid growth in size, and risk of bleeding may require intervention. Trans-arterial embolization (TAE) has been proposed for the treatment for giant hemangiomas of the liver, either alone or as an adjunct prior to definitive surgery. The purpose of this report is to present a case of a female patient with a giant symptomatic liver hemangioma that was referred to our outpatient hepatobiliary/pancreas (HBP) clinic. The patient was initially treated by TAE of the feeding vessels, followed by open surgery in the form of a non-anatomic left lateral hepatectomy.